The 12-year-old cocaine smuggler - Montorio, Benito ([Australia] : BBC, 2007)
What do 12-year-old, convicted cocaine smuggler Claudia,'laundry woman' Marcela Choce and the Bolivian President have in common? This World investigates the extent to which Moracles has managed to fulfil his election promise to oppose Anti-Narcotics Law 1008-which currently accounts for over 70 per cent of the women in the harsh Bolivian prison San Sebastion - and change the lives of people like Claudia and Marcela.
Narrator: Jason Isaacs ; film editor, Jay Taylor ; editor, Karen O'Connor.
dvd format
Keywords: Drug abuse; Cocaine industry; Smuggling